2021
DOI: 10.1177/02654075211046587
|View full text |Cite
|
Sign up to set email alerts
|

Affection deprivation during the COVID-19 pandemic: A panel study

Abstract: This study examined the longer-term effects of the COVID-19 lockdowns on relational communication and mental health. Specifically, the study used the theoretic premises of Affection Exchange Theory (AET: Floyd, 2006 ) to hypothesize connections between affection deprivation and several indices of mental health, including loneliness and depression. The study used a panel design to recruit participants at different time points during the COVID-19 lockdowns. We employed growth modeling to examine how affection de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…However, whether romantic partners cohabited emerged as a moderator for the association between guideline adherence and amount of affectionate touch: those who cohabited reported that greater adherence to distancing guidelines was associated with less affectionate touch, whereas, for those who were not cohabiting, the opposite was the case ( Burleson et al, 2022 ). Floyd’s (2006) Affection Exchange Theory also offers insight into affection during the pandemic, with individuals experiencing affection deprivation across relationships during COVID-19’s early stages ( Hesse et al, 2021 ). That deprivation was also related to increased stress, loneliness, and depression over a 6-week period, but unrelated to life satisfaction or happiness ( Hesse et al, 2021 ).…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, whether romantic partners cohabited emerged as a moderator for the association between guideline adherence and amount of affectionate touch: those who cohabited reported that greater adherence to distancing guidelines was associated with less affectionate touch, whereas, for those who were not cohabiting, the opposite was the case ( Burleson et al, 2022 ). Floyd’s (2006) Affection Exchange Theory also offers insight into affection during the pandemic, with individuals experiencing affection deprivation across relationships during COVID-19’s early stages ( Hesse et al, 2021 ). That deprivation was also related to increased stress, loneliness, and depression over a 6-week period, but unrelated to life satisfaction or happiness ( Hesse et al, 2021 ).…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“… Floyd’s (2006) Affection Exchange Theory also offers insight into affection during the pandemic, with individuals experiencing affection deprivation across relationships during COVID-19’s early stages ( Hesse et al, 2021 ). That deprivation was also related to increased stress, loneliness, and depression over a 6-week period, but unrelated to life satisfaction or happiness ( Hesse et al, 2021 ). These findings highlight the critical roles that physical distance and touch play in relationships, as well as the interplay between adaptive relationship processes such as affection and warmth and external COVID-19-related stressors as proposed by the adapted VSA model ( Pietromonaco & Overall, 2021 ), particularly during a crisis that frequently requires physical distancing from others.…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“…The COVID-19 pandemic, along with government measures to control its spread, has perpetuated such negative environments for many people across the world. Nationwide lockdowns and widespread surveillance thwart people’s feelings of autonomy and freedom and significantly reduces people’s ability to connect with others, while job insecurity can frustrate individuals’ need for competence ( Calvo et al, 2020 ; Cantarero et al, 2021 ; Hesse et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these studies, other researchers have contributed to understanding how loneliness occurred during the COVID-19 pandemic. For example, loneliness continued to correlate with detrimental outcomes during the pandemic that were known correlates prior to the pandemic, such as affection deprivation ( Hesse et al, 2021 ), feeling underbenefited in relationships ( Holmstrom et al, 2021 ), and depression and anxiety ( Hoffart et al, 2020 ). This is important because, in general, most studies found that loneliness increased during the first year of the pandemic (e.g., Bu et al, 2020 ; Hoffart et al, 2020 ; Killgore et al, 2020 ; Li & Wang, 2020 ).…”
Section: Loneliness Prevalence Before and During The Covid-19 Pandemicmentioning
confidence: 99%